2006
DOI: 10.1139/w05-142
|View full text |Cite
|
Sign up to set email alerts
|

Model plants for studying the interaction between Methylobacterium mesophilicum and Xylella fastidiosa

Abstract: Over the last few years, endophytic bacterial communities associated with citrus have been studied as key components interacting with Xylella fastidiosa. In this study, we investigated the possible interaction between the citrus endophyte Methylobacterium mesophilicum SR1.6/6 and X. fastidiosa in model plants such as Catharanthus roseus (Madagaskar periwinkle) and Nicotiana clevelandii (Clevelands tobacco). The aim of this study was to establish the fate of M. mesophilicum SR1.6/6 after inoculation of C. roseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
24

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 18 publications
3
43
0
24
Order By: Relevance
“…Shifts in endophytic bacterial communi-ties are therefore expected to occur after bacterial inoculation. This is a phenomenon that has been observed after inoculation of Madagascar periwinkle (Catharanthus roseus) and Cleveland tobacco (Nicotiana clevelandii) plants with Methylobacterium mesophilicum (1).…”
mentioning
confidence: 92%
“…Shifts in endophytic bacterial communi-ties are therefore expected to occur after bacterial inoculation. This is a phenomenon that has been observed after inoculation of Madagascar periwinkle (Catharanthus roseus) and Cleveland tobacco (Nicotiana clevelandii) plants with Methylobacterium mesophilicum (1).…”
mentioning
confidence: 92%
“…community and its interactions with X. fastidiosa [6,12]. The results of these studies found the pathogenic bacterium X. fastidiosa caused a shift in the indigenous endophytic community structure [13]. Genetically modified Enterobacter cloacae was able to colonize plants and to induce shifts in bacterial communities associated with citrus seedlings [14].…”
Section: Introductionmentioning
confidence: 99%
“…Com esta colonização sistêmica da planta, estas bactérias podem alterar as condições fisiológicas e morfológicas do hospedeiro, além de atuar sobre as populações de outros microrganismos presentes no interior da planta (ANDREOTE et al, 2004;ANDREOTE et al, 2006). Entre as enzimas produzidas por estes microrganismos, podem ser citadas amilases (STAMFORD et al, 2001), exolevanases (MENENDEZ et al, 2002), quitinases (PLEBAN et al, 1997), glucanases (MOY et al, 2002) e proteases (REDDY et al, 1996), as quais podem atuar em processos importantes na interação microrganismo-planta.…”
Section: )unclassified
“…estudos mostram que a produção de biofilme pode ser dependente da produção de moléculas de quorum sensing (DAVIES et al, 1998;NIETO-PEÑALVER et al, 2006), e que a formação de biofilme sobre a planta pode ser a primeira etapa para a colonização endofítica na interação Methylobacterium-planta (ANDREOTE et al, 2006), sugerindo a importância do entendimento destes processos envolvidos na interação bactéria-planta.…”
Section: Biofilmes Bacterianos E Comunicação Celular (Quorum Sensing)unclassified